PERSEPSI SISWA TERHADAP MATERI DAN METODE PEMBELAJARAN MENYIMAK - Farida Nugrahani; Ika Setyaningrum; Tiyas Aning Susanti; Sumarti; Lastri Hidayati; Maria Chrismawati Kartikasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore students' perceptions of the integration of materials and methods in listening instruction. This study is a descriptive qualitative study. The subjects were 30 high school students at State Elementary School 1 Lumbungkerep, Klaten, who were selected purposively. Data were collected through semi-structured interviews, member checking, and field notes, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results revealed two main themes: first, in the material dimension, students complained about high speaking speed, difficult to recognize foreign vocabulary, unfamiliar accents, and long recording durations that were tiring, but they really liked video- or image-based materials and stories that were relevant to their daily lives. Second, in the method dimension, students positively assessed the provision of apperception and key vocabulary, selective note-taking of important points, pauses during recordings, and discussions with peers. These methods were perceived to reduce anxiety, increase focus, and build self-confidence. In conclusion, student perceptions reflect cognitive and affective dynamics that require conscious management of the pace of material presentation, bridging vocabulary and accent gaps, integrating visual supports, and designing activities that accommodate metacognitive stages and collaborative discussions. The implication is that educators need to develop listening instructional designs that are more responsive to students' authentic experiences.